Pour un enseignement aspectuo-modal et illustré des temps du passé - Gezundhajt, Henriette (Canadian Journal of Applied Linguistics, 2010)
Accepted ideas about past tense in French leave traces that are very hard to erase from our learners’ minds. If imparfait is linked to duration, how can we explain: J’attrapais mon livre quand le téléphone a sonné? What should we think of verbs that take the être auxiliary with the passé composé tense and that are supposedly movement verbs? Are devenir, marcher or courir to be considered as exceptions? Is it enough to teach mnemonic tricks like the acronym Dr Mrs Vandertrampp? Multimedia can help us to transmit more appropriate aspectual concepts from enunciative theories like progress, boundaries or location in relation to a beginning or an end.